EPIDEMIOLOGY OF BONE TUMORS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Primary bone tumors are uncommon and this has certainly contributed to the scarcity of data about their relative frequency, and to the limited understanding of the risk factors. Overall, bone sarcomas account for 0.2% of all malignancies, and the adjusted incidence rate for all bone and joint malignancies is 0.9 per 100,000 persons per year, while the 5-year overall survival rate is 67.9%. The age specific incidence rates of bone sarcomas show a bimodal distribution, with a first peak occurring in the second decade, and a second peak occurring in patients older than sixty, in relation with the age distribution of the main histological subtypes.